Using Body Motion Capture for the Analysis of Disabilityin Upper or Lower Limbs. Use Case: hemiplegia - Briseño Cerón, Abraham; Domínguez Ramírez, Omar A.; Saucedo Ugalde, Ismaylia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2012)
All objects can have movement and their study is important to perform a characterizationas natural as possible. The locomotion movement of the human skeletal system is complex. Analysis,modeling and representation of the movements is a difficult task, the development of information technologies to capture motion trajectories, allow to save time and effort for the design and development of support tools for areas such as physiotherapy. In this research we use a motion capture device with eight cameras, 34 markers organized which are placed to identify each body segment and basic bodyarticulation. The capture and representation of body movements in hemiplegia people is using with3D tools, allowing to check, calculate and simulate continuously and have reliable results about this disability.